The role of the crop in poultry production. Issue 3 (1st September 2016) - Classen, H.L.; Apajalahti, J.; Svihus, B.; Choct, M.
Abstract : The importance of the crop is often underestimated in poultry production. In addition to storing ingested feed, it also can impact nutrient digestion by digesta softening and the initial activity of feed (endogenous and exogenous) and microbial enzymes. The crop represents the first major defence against poultry pathogens and zoonotic organisms with well established adaptive and innate immune function, and a lactobacilli dominated microbiota capable of reducing the passage of these organisms further along the digestive tract. However, the potential to improve bird productivity and health, as well as affect meat and egg safety, are influenced by the nature of the diet, and in particular feed entry and extended presence in the crop. This is required to promote lactobacilli fermentation, the production of lactic acid and other volatile fatty acids, and the lowering of crop pH. Management practices such as meal feeding and the use of lighting programs with extended dark periods encourage crop utilisation. Further, the use of feed additives such as prebiotics and probiotics may enhance crop function, which in turn contributes to well-being of the entire digestive tract. A healthy and functional crop, along with other segments of digestive tract, has increased importance in an era of reduced antibiotic use in poultry feeds.